Vitamin D Deficiency and Vasovagal Syncope in Children and Adolescents - Qingyou Zhang; Yan Sun; Chunyu Zhang; Jianguang Qi; Junbao Du (Frontiers Media S.A., 2021)
Aims: To investigate the association of vitamin D deficiency with cardiovascular autonomic nervous system function in children and adolescents with vasovagal syncope (VVS).Methods: This study recruited 76 pediatric patients with VVS and 15 healthy children. The 25-hydroxyvitamin D levels in serum among the participants were evaluated. Heart rate variability analysis including SDNN, rMSSD, and SDANN was tested in patients with VVS. The correlation between indices of time-domain analysis and serum vitamin D status of the children with VVS was investigated.Results: In this work, 25-hydroxyvitamin D levels in serum among VVS cases remarkably decreased compared with those among healthy controls (48.76 ± 19.25 vs. 67.62 ± 15.46 nmol/L, p < 0.01). The vitamin D deficient patients with VVS exhibited a lower rMSDD value compared to the non-deficient group with VVS (45.56 ± 16.87 vs. 61.90 ± 20.38 ms, p < 0.001, respectively). Pearson correlation analysis indicated that serum 25-hydroxyvitamin D levels had positive correlation with rMSDD values (r = 0.466, p < 0.001).Conclusions: As suggested by our data, VVS children and adolescents with vitamin D deficiency may have cardiac autonomic dysfunction and cardiac vagal tone decreases with the reduction in vitamin D level.